Role and Significance of Bioactive Substances in Sputum in the Diagnosis of Lung Cancer - Yuming JIN; Zixuan CHEN; Quan CHEN; Leihao SHA; Cheng SHEN (Chinese Journal of Lung Cancer, 2021)
The incidence rate of lung cancer is one of the highest incidence of malignancies in China. The gold standard for diagnosis requires pathological examination or cytological examination of biopsy. The invasive and sensitive nature of the two limits their use. Sputum contains a large number of nucleic acids and proteins, which is a good reflection of lung function. Lung cancer tissue will also affect the biological components in sputum. The detection of bioactive substances in sputum can contribute to the diagnosis of lung cancer. Based on the current research results at home and abroad, this paper reviews the bioactive substances in sputum that can be used for the diagnosis of lung cancer.